Selective vulnerability of human-induced pluripotent stem cells to dihydroorotate dehydrogenase inhibition during mesenchymal stem/stromal cell purification - Al-Akashi, Ziadoon; Zujur, Denise; Kamiya, Daisuke; Kato, Tomohisa; Kondo, Toru; Ikeya, Makoto (Frontiers in Cell and Developmental Biology, 2023)
The use of induced mesenchymal stem/stromal cells (iMSCs) derived from human induced pluripotent stem cells (hiPSCs) in regenerative medicine involves the risk of teratoma formation due to hiPSCs contamination in iMSCs. Therefore, eradicating the remaining undifferentiated hiPSCs is crucial for the effectiveness of the strategy. The present study demonstrates the Brequinar (BRQ)-induced inhibition of dihydroorotate dehydrogenase (DHODH), a key enzyme in de novo pyrimidine biosynthesis, selectively induces apoptosis, cell cycle arrest, and differentiation; furthermore, it promotes transcriptional changes and prevents the growth of 3-dimensional hiPSC aggregates. Contrastingly, BRQ-treated iMSCs showed no changes in survival, differentiation potential, or gene expression. The results suggest that BRQ is a potential agent for the effective purification of iMSCs from a mixed population of iMSCs and hiPSCs, which is a crucial step in successful iMSC-based therapy.